Work breakdown structure application for man-hours calculation in hull construction shipbuilding in Malaysia. Issue 1 (1st January 2019) - Wan Abd Rahman, W. A. Z.; Mohd Zaki, N. I.; Abu Husain, M. K.
Abstract: In Malaysia, the majority of oil & gas platform construction use fixed type substructure such as jacket type platform. To date, only one Semi-FPS has been constructed in Malaysia involving complex and challenging issues in the construction of hull substructure. Oil & gas project managers have difficulty to construct the hull and meet the project deadline due to lack of experience in shipbuilding knowledge. The aim of this paper is to define the work breakdown structure and to understand the linkages between work breakdown structure and man-hours development for actual shipbuilding project constructed at Malaysian shipyard, as it is the best tool to simplify the complexity of the project and define the complete and accurate work breakdown structure of a hull ship since it is an important and critical activity in every shipbuilding and Semi-FPS project. The methodology will involve the selection of actual Semi-FPS hull shipbuilding construction case study. The work breakdown structure and project man-hours development will be compared with the latest literature review. The investigation shows that the Product Work Breakdown Structure (PWBS) is the best method in identifying project man-hours in Hull Shipbuilding while the man-hours comparison shows the lower percentage of errors, i.e., 6.36% and 8.77% for the Hull Shipbuilding Structure parts. This concluded the acceptance of Estimator's Man-hours formula that used in the project case study which does not show any significant error when compared to Industrial Reference, i.e. Spon's Fabrication Norms for Offshore Structure. The lower Man-hours results compared to the Theoretical value will make the project more competitive and lower cost. Thus, this research will assist the Project Manager to have an idea in project schedule planning which will play a critical role during project management to identify the good WBS and project man-hours. This also leads to cost reduction in terms of man-hour optimization when the proper tasks and activities are clearly defined during WBS development.